GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 3312 species occurrences available in GBIF matching the query: TaxonKey: Medicago sativa L. Country: United States. The dataset includes 3312 records from 50 constituent datasets: 1 records from Phanerogamic Botanical Collections (S). 186 records from Consortium of California Herbaria. 21 records from Naturalis Biodiversity Center (NL) - Botany. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 5 records from MBM - Herbário do Museu Botânico Municipal. 8 records from Australia's Virtual Herbarium. 25 records from Kathryn Kalmbach Herbarium. 329 records from Consortium of California Herbaria. 26 records from iNaturalist research-grade observations. 57 records from CONN. 47 records from H.A. Stephens Herbarium. 7 records from University of Lethbridge Herbarium (LEA). 28 records from Louisiana State University Herbarium - Vascular Plants. 40 records from UCJEPS TAPIR Provider. 15 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 40 records from NMNH occurrence DwC-A. 125 records from Missouri Botanical Garden. 4 records from Botanical Research Intitute of Texas. 4 records from Mountain Invasion Research Network (MIREN) survey. 1 records from Australian National Herbarium (CANB). 41 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 5 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 29 records from Vascular Plant Collection. 30 records from Arizona State University Vascular Plant Herbarium. 46 records from Database Schema for UC Davis [Herbarium Labels]. 13 records from California State University, Chico. 1 records from Herbarium (UNA). 664 records from United States National Plant Germplasm System Collection. 43 records from The System-wide Information Network for Genetic Resources (SINGER). 17 records from USU-UTC Specimen Database. 2 records from Harvard University Herbaria. 51 records from Specimen Database of Colorado Vascular Plants. 664 records from EURISCO, The European Genetic Resources Search Catalogue. 24 records from Field Museum of Natural History (Botany) Seed Plant Collection. 132 records from New Mexico Biodiversity Collections Consortium database. 40 records from Colorado State University Herbarium. 13 records from MISS_DC_01MAR2006. 29 records from UA Herbarium. 209 records from R. L. McGregor Herbarium Vascular Plants Collection. 32 records from Botany Division, Yale Peabody Museum. 1 records from UPCB - Herbário do Departamento de Botânica. 21 records from Bernice P. Bishop Museum. 75 records from Michigan State University Herbarium Vascular Plants. 3 records from R - Herbário do Museu Nacional. 37 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 86 records from CZE National PGR Inventory. 4 records from Vascular Plant Herbarium, Oslo (O). 27 records from BUT Friesner Herbarium. 1 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 2 records from CAS Botany (BOT).
Keywords: GBIF; biodiversity; species occurrences